Financial performance assessment using the DuPont analysis - Puspitaningtyas, Zarah (Institute of Computer Science (IOCS), 2025)
This study aims to assess financial performance using DuPont analysis on technology sector companies listed on the Indonesia Stock Exchange with the three largest market capitalizations and positive net income in 2024. DuPont analysis is a method to evaluate company performance that serves to enhance a fundamental indicator, namely return on equity. Return on equity is used to measure the profit generated from the shareholders' perspective. The analysis is conducted using a quantitative descriptive design. The study results show that although DCII excels in the assessment of net profit margin and equity multiplier, the return on equity formed from the assessment of the three components: net profit margin, assets turnover, and equity multiplier indicates that MLPT outperforms DCII. This result indicates that MLPT is seen as more capable of providing potential investment opportunities than DCII for its investors